Trapped by law - Mustafa, Sami (Romawood, 2015)
During a dramatic night in March 2010, two brothers, Kefaet and Selami, rappers from Essen, are deported to Kosovo, a complete unknown country to them. Separated from their family and friends they try to cope with their situation and do everything in their power to return to Germany. But administration and asylum laws are standing in their way.--